Oil Shocks, Monetary Policy, and Stock Returns: A Case of Oil-based Economy - Alharbi, Abdullah M. H. (International Journal of Energy Economics and Policy, 2023)
This paper investigates the dynamic effects of oil price shocks on the Saudi stock market. It differs from previous work by examining the role of monetary transmission of oil shocks to stock returns via interest rate and credit channels. A Structural Vector Autoregressive model (SVAR) is used to trace the impacts of the underlying shocks. The results provide robust evidence in favor of a positive relationship between oil price volatility and stock market returns, which is aligned with the prevailing view on the oil impact in net oil-exporting countries. Variance decomposition results indicate that oil shocks are the key source of fluctuations in stock markets as they explain more than 25% of stock return variations. On the other hand, a weak over-all effect of monetary policy is concluded by this study using the two monetary policy channels. Unlike interest rate, credit channel is found to be relatively effective in the monetary policy transmission to stock market. The response of stock returns showed a positive significant impact of credit shocks, but a negligible effect of interest rate shocks. The outcome of this paper is considered plausible in an oil-based economy with fixed-exchange rate regime.